2022
DOI: 10.1021/acs.cgd.1c01268
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Metal–Organic Frameworks as Ratiometric Sensors

Abstract: In the last two decades, metal−organic frameworks (MOFs) have appeared as new multifunctional materials that show a variety of framework architectures depending on the choice of metal ions and ligands. Among several features that have been displayed by MOF, one of the important properties is its luminescent behavior that can arise from the ligand unit, metal ions, or the cavity guest molecules. Ratiometric fluorescence (RF) sensors can be made by changing the fluorescence intensity of emission peaks associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 247 publications
(415 reference statements)
2
39
0
Order By: Relevance
“…Compared with the free H 4 L and H 2 biim ligands, 1 exhibits a significant red-shifted emission at 443 nm (λ ex = 292 nm) and 2 shows a slightly red-shifted emission around 423 nm upon irradiation at 283 nm (Figure S6b and S6c). The results show that the fluorescence of 1 and 2 is mainly attributed to the ligand-to-ligand charge transfer (LLCT). , At present, the research of MOF luminescent sensing mainly employs the solution system as the medium, combined with the excellent water stability and solid-state fluorescent characteristics of 1 and 2 ; thus, the fluorescent spectra of H 4 L, 1 , and 2 in aqueous solution were further tested. It can be observed that they show intense emission at λ em = 348 nm (λ ex = 300 nm) for H 4 L, λ em = 350 nm (λ ex = 295 nm) for 1 , and λ em = 332 nm (λ ex = 290 nm) for 2 in aqueous suspension (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Compared with the free H 4 L and H 2 biim ligands, 1 exhibits a significant red-shifted emission at 443 nm (λ ex = 292 nm) and 2 shows a slightly red-shifted emission around 423 nm upon irradiation at 283 nm (Figure S6b and S6c). The results show that the fluorescence of 1 and 2 is mainly attributed to the ligand-to-ligand charge transfer (LLCT). , At present, the research of MOF luminescent sensing mainly employs the solution system as the medium, combined with the excellent water stability and solid-state fluorescent characteristics of 1 and 2 ; thus, the fluorescent spectra of H 4 L, 1 , and 2 in aqueous solution were further tested. It can be observed that they show intense emission at λ em = 348 nm (λ ex = 300 nm) for H 4 L, λ em = 350 nm (λ ex = 295 nm) for 1 , and λ em = 332 nm (λ ex = 290 nm) for 2 in aqueous suspension (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…MOFs possess unique and fascinating structural chemistry such as inorganic-organic hybrid network, 2 high surface area, 3 controllable pore size, 4 flexibility, 5 easy functionalization, 6 smooth tuning of their host-guest interaction 7 and good stability. 8 All these qualitative features of MOFs make them suitable for several potential applications such as sensing, [9][10][11] catalysis, [12][13][14] CO 2 sequestration, 15,16 magnetism, 17 gas adsorption, 18,19 separation, [20][21][22] bio-imaging, 23 drug delivery, 24 energy storage, 25 and proton conductance. 26 Interestingly, MOFs can potentially act as luminescent sensors and this application has been flourishing significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, fluorescent materials are in surging demands because of their ease in handling, swift response time, superior sensitivity, selectivity, repeatability, and easy mobility . Recently, the metal–organic frameworks (MOFs), a class of advanced porous compounds, turned out to be effective sensors. MOFs possess several qualitative characteristics such as a greater surface area, high stability, structural diversity, , nicely oriented guest interaction site, , purposefully rooted active sites, , and, more importantly, structure–property correlation bestow them as excellent luminescent sensors. However, for the real-time monitoring of the lethal ions and bio-relevant organic compounds, it is imperative for the sensor to have low detection limit, ultra-fast responsive time, highly selective with multicycle detection ability, and colorimetric response.…”
Section: Introductionmentioning
confidence: 99%